PERBANDINGAN KUALITAS KIMIA DAGING SAPI BRAHMAN CROSS DARI FEEDLOTER DAN PETERNAKAN RAKYAT DI WILAYAH LAMPUNG - Deva Cahyasari; Ali Husni; Liman Liman; Arif Qisthon (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the chemical quality (water content, fat content, and protein content) of Brahman Cross (BX) beef originating from feedloters and people's farms in Lampung Region. This research was carried out in November--December 2021 at the Slaughterhouse and Animal Nutrition and Feeding Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research method carried out in this study was a survey. The meat samples came from 12 cattles taken from the Slaughterhouse that has collaborated with feedloters and catlles broker. The variables observed in this study were water content, fat content, and protein content. The data used in this study consisted of primary data. Primary data obtained from observations and analyzed descriptively. The results showed that the best (lowest) water content came from people’s farms ranging from 74.13--76.39%, the best (highest) protein content came from feedloters ranging from 16.44--18.54%, and there is no difference in fat content between feedloters and people farms ranging from 2.32--2.56%. Keywords: Brahman Cross, Chemical quality, Feedloters, meat, People’s farms